1990
DOI: 10.1088/0029-5515/30/1/007
|View full text |Cite
|
Sign up to set email alerts
|

Ion heating and current drive from relaxation in decaying spheromaks in mesh flux conservers

Abstract: The plasma energy confinement in CTX mesh flux conservers appears to be dominated by relaxation fluctuations which drive current in the resistive plasma edge region. Strong ion heating is expected from these relaxation processes. The paper presents new data, from previously studied decaying discharges, which show impurity oxygen ion Doppler temperatures much above the Thomson scattering electron temperature. In addition, using the standard MHD equilibrium model by Knox et al., and the resistivity model previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
10
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
(65 reference statements)
4
10
0
Order By: Relevance
“…2,3,6 Another observation consistent with edge-dominated helicity decay was that both x E and the global magnetic energy decay time (r^) did not depend on the central electron temperature. 2 Observations and conditions in other spheromak devices are also consistent with this model.…”
mentioning
confidence: 63%
“…2,3,6 Another observation consistent with edge-dominated helicity decay was that both x E and the global magnetic energy decay time (r^) did not depend on the central electron temperature. 2 Observations and conditions in other spheromak devices are also consistent with this model.…”
mentioning
confidence: 63%
“…However, we now present results from SPHEX which for the first time show that (vxb) is nonzero, and of the right magnitude to drive the current. We shall show that both single-mode and turbulent dynamos are present, although the former forms an ''antidynamo" opposing the applied electric field [12].…”
mentioning
confidence: 84%
“…It has been demonstrated that particle transport [8] and energy transport [3,4] are enhanced during periods of the discharge in which there is strong relaxation activity. Together with strong plasma relaxation, a significant decrease in the magnetic field decay time (due to relaxation current drive in the resistive edge) and high ion temperatures (T| <> 5T e ) [3,9,10] have been observed. Charge exchange (CX) of these anomalously hot ions and subsequent escape of hot neutrals appear to dominate the energy balance of these plasmas.…”
Section: Introductionmentioning
confidence: 99%